2015
DOI: 10.4236/jbbs.2015.57028
|View full text |Cite
|
Sign up to set email alerts
|

Curricular Content Level of Complexity Is a Factor of Depression and Learning in Medical Students

Abstract: The aim of this paper was to analyze the impact of Human Physiology curriculum on depression and academic performance of medical students. Beck instrument was applied before exams' period to all students who voluntarily participated and the grades gotten in each of the three Human Physiology exams were correlated with all first year's averages. Descriptive and inferential statistics were carried out. We found a significant relationship between the complexity of Human Physiology curriculum and the number of cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The first standard emphasises deliberate structuring of learning content, tasks, and environments to promote the building of profession-specific competencies among students. Guzmán and Urrutia-Aguilar 70 attest to the importance of meticulous designing of physiology content to reduce its complexity, academic failure and frustration while supporting knowledge integration and comprehension. The design of health sciences curricula to create numerous opportunities for intertwining theoretical knowledge and authentic clinical tasks cannot be understated.…”
Section: Discussionmentioning
confidence: 99%
“…The first standard emphasises deliberate structuring of learning content, tasks, and environments to promote the building of profession-specific competencies among students. Guzmán and Urrutia-Aguilar 70 attest to the importance of meticulous designing of physiology content to reduce its complexity, academic failure and frustration while supporting knowledge integration and comprehension. The design of health sciences curricula to create numerous opportunities for intertwining theoretical knowledge and authentic clinical tasks cannot be understated.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, having a solid foundation of basic sciences was demonstrated to have a significant impact on further understanding of medical physiology (Guevara et al, 2015;Michael, 2006), it also provides evidence on how the role of active learning focusing on the student's perspective, can be used efficiently when teaching physiology. They demonstrated that among typical teaching strategies, active problem solving and collaborative learning yield consistently improved outcomes and positive students´ feedback.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is necessary to create a teaching training program specifically designed to strengthen the reflective ability on teaching practices that influences teachers to adopt new pedagogical referents (Urrutia et al, 2015). The challenge is to consider that, in educator training, the distance between declarative knowledge (theoretical knowledge) and practical knowledge (application knowledge) is still a big gap that will need to be narrowed by adding new teaching modalities based on praxis conceptions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation